Effects of hydrogen peroxide on plant performance, leaf histology, nutrient uptake, bioactive compounds and Rubisco gene expression in Mas Cotek (Ficus deltoidea Jack var. deltoidea Corner) - Nik Nurnaeimah Nik Muhammad Nasir
Ficus della idea (Mas cotek) has been given special emphasize by the Malaysian government and has identified as a potential commercial important medicinal herb due to its biological properties. However, Ficus deltoidea was recognized as a slow growing.The present study was carried out to investigate the effect of hydrogen peroxide on the growth and development, physiology leaf histology, bioactive compounds and Rubisco gene expression in Ficus deltoidea var. deltoidea. Various physiological, leaf histological, mineral uptake, biological and biochemical parameters were monitored during the growing period of March 2015 to May 2016 at field farm of Faculty of Bioresources and Food Industry, UniSZA, Besut Campus. The Ficus deltoidea plants were spray-treated with 0 (control), 8, 16, 30 and 60 mM hydrogen peroxide under field conditions. The experiment was arranged according to the completely randomized design (CRD) with eight replications. The DPPH scavenging assay, Follin-Ciocalteu, aluminum chloride colorimetric method, u¬glucosidase assay were done to determine antioxidant property by calculating the ICso value, to access effect on total phenolic and flavonoid contents and to access the effect of hydrogen peroxide on Vitexin and Isovitexin contents. While qualitative and quantitative Real-Time PCR and gel electrophoresis was done to access effects of hydrogen peroxide on Rubisco gene expression in the plant. The results showed that the application of 30 mM hydrogen peroxide significantly increased plant height, leaf number, syconium number, net photosynthetic rate, transpiration and stomatal conductance compared with other treatments and control. Leaf chlorophyll content, chlorophyll fluorescent, and leaf area were also increased. Hydrogen peroxide treatment at 60 mM provoked some changes in the leaves structure such as shrinkage of cells, smaller cell size, and thinner cell wall but without inducing oxidative stress. Hydrogen peroxide enhanced the mineral uptake. Hydrogen peroxide, particularly in the concentration of 30 mM, increased the antioxidant property, total phenolic and flavonoid contents, and the contents of Vitexin and Isovitexin. It was indicated that hydrogen peroxide had down-regulated Rubisco gene with between 1-5 folds gene expression changes as compared to an untreated plant. From this study, it can be concluded that spraying of 16 mM and 30 mM of hydrogen peroxide once a week should be used to enhance plants and to improve the antioxidant property of the herb.